A Review of Environmental Vulnerabilities Related to Nepal’s Graduation Process from Least Developed to a Developing Country Status - Adhikari, Ambika; Bhattarai, Keshav; Sharma, Basu (Journal of Foreign Affairs, 2022)
Nepal has long aspired to graduate from the Least Development Country (LDC) to Developing Country category as defined by the United Nations system. Nepal had met two of the three graduating criteria and could have technically graduated from the LDC status in 2015. However, based on the Nepal government’s request to defer the review, the new 2021 assessment by the United Nations Committee for Development Policy (CDP) recommended that the country should graduate from the LDC status by 2026. The graduation requires not only meeting pre-defined development-related thresholds, but also maintaining sustained improvements in at least two consecutive assessments in two of three areas: gross national income (GNI) per capita, human assets index (HAI), and economic and environmental vulnerability index (EnVI). Nepal’s economy is dependent on several environment-related factors such as agriculture, tourism, hydro-power, and natural resources. This economic development is also solidly tied to the environmental well-being of the country. The authors agree with the Nepal government’s desire to graduate from the LDC status. In this paper, we review the graduation process, assess indicators of the Environmental Vulnerability (EnVI), review the current situation with respect to environmental vulnerability, and point out where it needs to develop appropriate goals, policies, and programs to help the country graduate and join the ranks of developing countries.